The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/493170
|View full text |Cite
|
Sign up to set email alerts
|

HFEMutations in Caucasian Participants of the Hemochromatosis and Iron Overload Screening Study with Serum Ferritin Level <1000 μg/L

Abstract: BACKGROUND: Many patients referred for an elevated serum ferritin level <1000 μg/L are advised that they likely have iron overload and hemochromatosis.AIMS: To determine the prevalence ofHFEmutations in the hemochromatosis gene for 11 serum ferritin concentration intervals from 200 μg/L to 1000 μg/L in Caucasian participants in a primary care, population-based study.METHODS: The Hemochromatosis and Iron Overload Screening study screened 99,711 participants for serum ferritin levels, transferrin saturation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 12 publications
(12 reference statements)
1
19
0
2
Order By: Relevance
“…As a result of iron loss from menstruation and pregnancies, SF values in adult females only start to rise after 50 years of age, to plateau with median values of about 100 μg/l after 60 years. Values >200 μg/l in adult females show a significant age effect and are seen in 3%, 10% and 17% respectively of women aged 30–50 years, 50–70 years and >70 years (Ogilvie et al , ; Adams et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of iron loss from menstruation and pregnancies, SF values in adult females only start to rise after 50 years of age, to plateau with median values of about 100 μg/l after 60 years. Values >200 μg/l in adult females show a significant age effect and are seen in 3%, 10% and 17% respectively of women aged 30–50 years, 50–70 years and >70 years (Ogilvie et al , ; Adams et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…13,18 The NPV of SF was high overall and thus this marker was effective at ruling out subjects with an unaffected genotype. We found that the Best Practice Advocacy Centre New Zealand (BPACNZ) advice that SF >700 μg/L is an indicator of HH 8 was inaccurate.…”
Section: Haemochromatosis In New Zealandmentioning
confidence: 99%
“…3,5 Although there is strong evidence to justify the need for pre-symptomatic detection of this condition, one of the problems faced by primary care physicians in identifying HH is that symptoms are often absent or mimic those found in other common conditions. 13,14 Previously undiagnosed C282Y homozygotes with SF values that remain <1000 μg/L are at low risk for developing HH signs and symptoms. 9,10 Abnormalities in iron biochemical assays are often the first indicator of HH, and it is widely accepted that transferrin saturation (TS) and SF are the best initial tests for HH.…”
Section: Introductionmentioning
confidence: 99%
“…L'hyperferritinémie est fréquente, retrouvée chez 13 % des personnes dans une population donnée [11]. Toute hyperferritinémie impose d'en découvrir l'étiologie et de préciser s'il existe un risque de surcharge en fer au niveau de l'organisme.…”
Section: La Démarche Diagnostique Devant Une Hyperferritinémieunclassified
“…Elle est fréquente en Europe occidentale, atteint 2 à 5 ‰ personnes en France, jusqu'à 1 % en Irlande [38]. Dans une population donnée, la mutation homozygote C282Y était retrouvée chez 3 % des personnes ayant une hyperferritinémie [11].…”
Section: Syndrome Métabolique Et Hyperferritinémieunclassified